PENGARUH CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DENGAN SIZE DAN LEVERAGE SEBAGAI VARIABEL KONTROL - Desan Neo Romadhona; Prasetiono Prasetiono (Diponegoro Journal of Management, 2022)
This study aims to determine the effect of corporate governance on corporate social responsibility (CSR) with size and leverage as control variables. Corporate Governance is measured by board size, board independence, and female board representation. Meanwhile CSR is measured by using the ESG score. The data used in this study is secondary data and the population of this study was 756 companies listed on the Indonesia Stock Exchange in the 2016-2020. Based on the purposive sampling method, as a method of data collection, a total of 66 companies have met the criteria set as research samples. Multiple regression analysis used to test the research hypotheses using the IBM SPSS version 26 program. The results show that board size has a significant positive effect on CSR disclosure. For board independence and board representation, it has a significant negative effect on CSR disclosure. While the size control variable has a significant positive effect on CSR disclosure and the leverage control variable has insignificant negative effect on the CSR disclosure